Effectiveness of Farmer Producer Organizations (FPOs) at Different Growth Stages in Transitioning to Secondary Agriculture - Anand, Shreya; Ghosh, Souvik; Mukherjee, Anirban (Indian Journal of Extension Education, 2023)
FPOs are gaining recognition as institutions for improving the small holders’ farming in India. However, the extent to which FPOs effectively facilitate the transition to secondary agriculture for the sustainable development of these farmers has not been extensively studied. This study was conducted during 2022-2023 to assess the effectiveness of randomly selected four FPCs in Bihar, which are functional for 1-3 years,>5 years, and >10 years. A random sample of 160 members, 40 from each FPC, was selected. The overall effectiveness of 50.55 % to 56.20 % in FPCs at their initial stage of functioning; while the FPCs being functional for more than 5 years and more than 10 years showed overall effectiveness of 60.03% and 68.40%, respectively. The FPC diversifying their products and performing processing, manufacturing, and marketing functions showed the highest effectiveness (68.40%) as compared to the FPCs dealing with single products and/or performing selected functions like providing agricultural inputs, and marketing. A one-way ANOVA followed by Post hoc test revealed significant variations in the effectiveness of FPOs. The present study provides valuable insights into the role of FPOs in the transition to secondary agriculture providing better income and livelihoods to farmers.